Frailty and Mortality Risk in COPD: A Cohort Study Comparing the Fried Frailty Phenotype and Short Physical Performance Battery - Brighton LJ; Nolan CM; Barker RE; Patel S; Walsh JA; Polgar O; Kon SSC; Gao W; Evans CJ; Maddocks M; Man WDC (International Journal of COPD, 2023)
Lisa Jane Brighton,1 Claire M Nolan,2,3 Ruth E Barker,2,4,5 Suhani Patel,2,4 Jessica A Walsh,2 Oliver Polgar,2 Samantha SC Kon,2,4,6 Wei Gao,1 Catherine J Evans,1,7 Matthew Maddocks,1 William DC Man2,4,8,9 1Cicely Saunders Institute of Palliative Care, Policy and Rehabilitation, King’s College London, London, UK; 2Harefield Respiratory Research Group, Royal Brompton and Harefield Hospitals, Guy’s and St Thomas NHS Foundation Trust, London, UK; 3Division of Physiotherapy, College of Health, Medicine and Life Sciences, Brunel University London, London, UK; 4National Heart and Lung Institute, Imperial College, London, UK; 5Insight Innovation, Wessex Academic Health Science Network, Southampton, UK; 6Department of Respiratory Medicine, The Hillingdon Hospital NHS Trust, London, UK; 7Brighton General Hospital, Sussex Community NHS Foundation Trust, Brighton, UK; 8Harefield Pulmonary Rehabilitation Unit, Guy’s and St Thomas NHS Foundation Trust, London, UK; 9Faculty of Life Sciences & Medicine, King’s College London, London, UKCorrespondence: Lisa Jane Brighton, Cicely Saunders Institute, Bessemer Road, Denmark Hill, London, SE5 9PJ, UK, Tel +44 020 7848 5041, Email lisa.brighton@kcl.ac.ukBackground: Identifying frailty in people with chronic obstructive pulmonary disease (COPD) is deemed important, yet comparative characteristics of the most commonly used frailty measures in COPD are unknown. This study aimed to compare how the Fried Frailty Phenotype (FFP) and Short Physical Performance Battery (SPPB) characterise frailty in people with stable COPD, including prevalence of and overlap in identification of frailty, disease and health characteristics of those identified as living with frailty, and predictive value in relation to survival time.Methods: Cohort study of people with stable COPD attending outpatient clinics. Agreement between frailty classifications was described using Cohen’s Kappa. Disease and health characteristics of frail versus not frail participants were compared using t-, Mann–Whitney U and Chi-Square tests. Predictive value for mortality was examined with multivariable Cox regression.Results: Of 714 participants, 421 (59%) were male, mean age 69.9 years (SD 9.7), mean survival time 2270 days (95% CI 2185– 2355). Similar proportions were identified as frail using the FFP (26.2%) and SPPB (23.7%) measures; classifications as frail or not frail matched in 572 (80.1%) cases, showing moderate agreement (Kappa = 0.469, SE = 0.038, p < 0.001). Discrepancies seemed driven by FFP exhaustion and weight loss criteria and the SPPB balance component. People with frailty by either measure had worse exercise capacity, health-related quality of life, breathlessness, depression and dependence in activities of daily living. In multivariable analysis controlling for the Age Dyspnoea Obstruction index, sex, BMI, comorbidities and exercise capacity, both the FFP and SPPB had predictive value in relation to mortality (FFP aHR = 1.31 [95% CI 1.03– 1.66]; SPPB aHR = 1.29 [95% CI 0.99– 1.68]).Conclusion: In stable COPD, both the FFP and SPPB identify similar proportions of people living with/without frailty, the majority with matching classifications. Both measures can identify individuals with multidimensional health challenges and increased mortality risk and provide additional information alongside established prognostic variables.Keywords: respiratory disease, chronic obstructive pulmonary disease, frailty, survival